2020
DOI: 10.1155/2020/5783748
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Combined Model Based on Platelet Count and Albumin to Rule out High-Risk Varices in Liver Cirrhosis

Abstract: Background. The Baveno VI criteria based on platelet count and liver stiffness, measured by transient elastography (TE), have been proposed to rule out high-risk varices (HRV) defined as medium or large-sized varices or the presence of high-risk stigmata (cherry red spots and red wale marks). However, TE is not available in all hospitals. Recently, the Rete Sicilia Selezione Terapia hepatitis C virus (RESIST-HCV) criteria recommended that cirrhotic patients with a platelet count>120000/μL and serum albumin&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These criteria have been validated in patients with active hepatitis C virus (HCV) or HBV infection (8) and in patients with nonalcoholic fatty liver disease (9), and they are limited by the use of transient elastography (TE), a tool that could not be available in nonreferral centers and in low-resource countries. We previously demonstrated that Rete Sicilia Selezione Terapia HCV (RESIST-HCV) biochemical-based criteria, including only platelet count and serum albumin, assessed before direct-acting antiviral agents (DAAs), showed a similar accuracy to that of elastography-based criteria for predicting the presence of HRV (10)(11)(12). It is important to take into account that all noninvasive criteria for HRV prediction have been evaluated in patients with HCV with compensated advanced chronic liver disease before DAAs alone.…”
Section: Introductionmentioning
confidence: 99%
“…These criteria have been validated in patients with active hepatitis C virus (HCV) or HBV infection (8) and in patients with nonalcoholic fatty liver disease (9), and they are limited by the use of transient elastography (TE), a tool that could not be available in nonreferral centers and in low-resource countries. We previously demonstrated that Rete Sicilia Selezione Terapia HCV (RESIST-HCV) biochemical-based criteria, including only platelet count and serum albumin, assessed before direct-acting antiviral agents (DAAs), showed a similar accuracy to that of elastography-based criteria for predicting the presence of HRV (10)(11)(12). It is important to take into account that all noninvasive criteria for HRV prediction have been evaluated in patients with HCV with compensated advanced chronic liver disease before DAAs alone.…”
Section: Introductionmentioning
confidence: 99%
“…These are much less validated than Baveno VI criteria. The RESIST-HCV criteria were specifically developed for hepatitis-C related cirrhosis and proposed a combination of platelet count more than 120000 cells/ml and serum albumin more than 3.6 g/dL [10,12]. However, with increasing HRV prevalence, as shown in the study by Sharma et al [25], and similar to what occurs with the expanded Baveno VI criteria, the NPV decreases to below 95%.…”
Section: Extrapolation Of Baveno VI Criteria To Other Elastography Me...mentioning
confidence: 98%
“…Indeed, the term ‘compensated advanced chronic liver disease’ (cACLD) was coined to reflect the continuum of severe fibrosis and cirrhosis in patients with ongoing chronic liver disease [5]. Doing a gastroscopy in all patients with cACLD would result in unnecessary load to endoscopy services, and would be low yield, as the prevalence of high-risk varices in these patients is around 10–15% (Table 1) [6–29,30 ▪▪ ,31,32 ▪▪ ,33].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we also stratified the patients on the basis of resisting HCV scores [RESIST-HCV low risk (LR) if they had PLT count >120,000/L and serum albumin 3.6 g/dL or RESIST-HCV high risk (HR) if they had PLT count <120,000/L or serum albumin <3.6 g/dL] to Monitor Progression of Esophageal Varices [30][31][32].…”
Section: Patientsmentioning
confidence: 99%